PEMBERONTAKAN PEREMPUAN BALI TERHADAP DISKRIMINASI KELAS DAN GENDER: KAJIAN FEMINIS NOVEL TARIAN BUMI KARYA OKA RUSMINI - Dara Windiyarti (Humaniora, 2008)
This paper discusses level and gender descrimination in Tarian Bumi, a novel written by Oka Rusmini (2004). Level and gender descrimination can be seen through the differences in actions, statuses, and positions between the brahmana level and the sudra level, and between the male and female characters, not only in domestic issues, but also in publicissues. The differences in actions, statuses, and positions are manifest in the oppression of the weaker level (sudra and female) by the stronger level (brahmana and male). This paper adopts a feminist approach to investigate the level and gender descrimination as found in the novel.